Revolution trough constitution: the Brazilian’s directive constitution debate - Bercovici, Gilberto (Revista de Investigações Constitucionais, 2014)
The article discusses the phenomenon known as Directive Constitution and points out that several constitutions enacted in the 20th and 21st centuries in peripheral countries seek to bind the legislature to a constitutional project, thus establishing a political line of action that ensures the progressive construction – through the law – of a new social and economic reality, therefore overcoming underdevelopment.